ESG performance and business risk—Empirical evidence from China's listed companies - Fei Chen; Yue-hu Liu; Xue-zhao Chen (Innovation and Green Development, 2024)
Under the dual-carbon background, enterprises' ESG performance and sustainable development capability have become a topic of great concern to all sectors of society. The ESG industry in China is very young, and there isn't much research looking at how ESG performance relates to business risk for corporations. This paper empirically tests the impact of firms' ESG performance on their business risk. It discusses the mechanism from the viewpoints of financing constraints and agency costs, the moderating role of economic policy uncertainty, and the analysis of differences in corporate size. The results indicate that firms with strong ESG performance experience a significant reduction in business risk. These firms face lower financing constraints and agency costs, which contribute to the mitigation of business risk. Furthermore, economic policy uncertainty moderates the link between ESG performance and business risk. Additionally, the influence of ESG performance on business risk is more significant in larger-scale companies.